Correlation dynamics of nitrogen vacancy centers located in crystal cavities - Abdel-Haleem Abdel-Aty (Nature Portfolio, 2020)
Abstract In this contribution, we investigate the bipartite non-classical correlations (NCCs) of a system formed by two nitrogen-vacancy (N-V) centers placed in two spatially separated single-mode nanocavities inside a planar photonic crystal (PC). The physical system is mathematically modeled by time-dependent Schrödinger equation and analytically solved. The bipartite correlations of the two N-V centers and the two-mode cavity have been analyzed by skew information, log-negativity, and Bell function quantifiers. We explore the effects of the coupling strength between the N-V-centers and the cavity fields as well as the cavity-cavity hopping constant and the decay rate on the generated correlation dynamics. Under some specific parameter values, a large amount of quantum correlations is obtained. This shows the possibility to control the dynamics of the correlations for the NV-centers and the cavity fields.